E-Collaboration Impacts in Australia and Hong Kong - Bajwa, D.; Lewis, F.; Pervan, Graham; Lai, V. (Dept. of Business Systems, University of Wollongong & School of Computing and Information Technology, Monash University, 2003-, 2014)
This paper investigates e-collaboration impacts across organizations in Australia and Hong Kong. The two regions were selected because of diversity in geographical dispersion and cultural differences. A myriad of e-collaboration activities were included in the study. Data collected and analyzed from 73 organizations in Australia and 94 organizations in Hong Kong suggests that there are no significant differences in the level of electronic support for collaboration activities in both the regions. However, significant differences were detected in the perceived impacts of e-collaboration between the two study regions. Interestingly, there was high level of agreement on ranking of e-collaboration activities and perceived e-collaboration impacts in both the regions. Implications of our findings for practice and research are discussed.